Detection and analysis of enamel cracks by ICG‐NIR fluorescence dental imaging. Issue 1 (9th June 2020) - Li, Zhongqiang; Holamoge, Yoshita V.; Li, Zheng; Zaid, Waleed; Osborn, Michelle L.; Ramos, Alexandra; Miller, Jacob T.; Li, Yanping; Yao, Shaomian; Xu, Jian
Abstract: Cracked teeth are the third most common cause of tooth loss, but there is no reliable imaging tool for the diagnosis of cracks. Here, we demonstrate the feasibility of indocyanine green near‐infrared fluorescence (ICG‐NIRF) dental imaging for the detection of enamel cracks and enamel–dentin cracks in vitro in the first (ICG‐NIRF‐I, 700–950 nm) and second (ICG‐NIRF‐II, 950–1700 nm) imaging windows with transmission excitation light, and compared ICG‐NIRF with conventional NIR illumination‐II (NIRi‐II) and X‐ray imaging. Dentin cracks were detected by CT scan, while most enamel cracks, undetectable under X‐ray imaging, were clearly visible in NIR images. We found that ICG‐NIRF‐II detected cracks more effectively than NIRi‐II, and that light orientation is an important factor for crack detection: an angled exposure obtained better image contrast of cracks than parallel exposure, as it created a shadow under the crack. Crack depth could be evaluated from the crack shadow in ICG‐NIRF and NIRi‐II images; from this shadow we could determine crack depth and discriminate enamel–dentin cracks from craze lines. Cracks could be observed clearly from ICG‐NIRF images with 1‐min ICG tooth immersion, although longer ICG immersion produced images with greater contrast. Overall, our data show that ICG‐NIRF dental imaging is a useful tool for diagnosing cracked teeth at an early stage. Abstract : Cracked teeth are a common cause of tooth loss, but there is no reliable imaging tool for the diagnosis of cracks. Here, we demonstrate the feasibility of indocyanine green near‐infrared fluorescence (ICG‐NIRF) dental imaging for the detection of enamel cracks and enamel–dentin cracks in vitro . Overall, ICG‐NIRF dental imaging is a useful tool in the diagnosis of cracked teeth at an early stage.